2007
DOI: 10.1186/1475-2891-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an open-label pilot study with high-dose EPA/DHA concentrates on plasma phospholipids and behavior in children with attention deficit hyperactivity disorder

Abstract: BackgroundAttention deficit hyperactivity disorder (ADHD) is the most common neurological condition in children. This pilot study evaluated the effects of high-dose eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) supplementation on the isolated plasma phospholipids and behavior in children with ADHD (primarily inattentive subtype and combined subtype).MethodsNine children were initially supplemented with 16.2 g EPA/DHA concentrates per day. The dosage was adjusted dependent on the ratio of arachidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 30 publications
2
76
0
Order By: Relevance
“…Two planned comparisons yielded effect sizes ranging from small (O3 vs. placebo) to large (O3+AM vs. PBO+AM) on the YMRS, the unfiltered measure of manic symptoms, but not on the KMRS, the filtered measure. This may indicate potential benefits of O3 for co-occurring problems such as inattention, hyperactivity, and aggressive behavior, which are assessed on the unfiltered YMRS and have been reported to improve with O3 in prior studies (Sinn and Bryan 2007;Sorgi et al 2007). It is of note that group differences in depression trajectories were primarily on KDRS scores, a filtered rating of depression, rather than the CDRS-R (which is more likely to capture symptoms of comorbid conditions), possibly because PEP was designed to specifically treat mood, and the KDRS is a more precise measure of depression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two planned comparisons yielded effect sizes ranging from small (O3 vs. placebo) to large (O3+AM vs. PBO+AM) on the YMRS, the unfiltered measure of manic symptoms, but not on the KMRS, the filtered measure. This may indicate potential benefits of O3 for co-occurring problems such as inattention, hyperactivity, and aggressive behavior, which are assessed on the unfiltered YMRS and have been reported to improve with O3 in prior studies (Sinn and Bryan 2007;Sorgi et al 2007). It is of note that group differences in depression trajectories were primarily on KDRS scores, a filtered rating of depression, rather than the CDRS-R (which is more likely to capture symptoms of comorbid conditions), possibly because PEP was designed to specifically treat mood, and the KDRS is a more precise measure of depression.…”
Section: Discussionmentioning
confidence: 92%
“…O3 may improve symptoms of many psychiatric disorders in youth including mood disorders (Wozniak et al 2007;Clayton et al 2009;McNamara et al 2010;Sarris et al 2012), autism (Amminger et al 2007), attention-deficit/hyperactivity disorder (ADHD) (Sinn and Bryan 2007;Sorgi et al 2007), and psychosis (Amminger et al 2010). O3 has also been shown to significantly improve cardiovascular and metabolic health and decrease body fat, both independently and in combination with regular exercise (Hill et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…showing some improvements (195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205) and others finding no effect (206)(207)(208)(209)(210)(211)(212)(213)(214) . These trials have been reviewed many times, with differing conclusions.…”
Section: Neurocognitive Healthmentioning
confidence: 99%
“…Six more studies of varying quality, two of them were open-label studies, supplemented n-3 fatty acids alone (Voigt et al, 2001;Hiramaya et al, 2004;Joshi et al, 2006;Sorgi et al, 2007;Vaisman et al, 2008;Gustafsson et al, 2010). Only the openlabel studies showed a significant effect of ALA (400 mg/d) or very high doses of EPA/DHA (16 g/d) on behavioural outcomes (Joshi et al, 2006;Sorgi et al, 2007). Three of the four randomized controlled trials supplementing DHA (+EPA) point into the same direction (Voigt et al, 2001;Vaisman et al, 2008;Gustafsson et al, 2010) (figure 2).…”
Section: Evidence From Diseased Populationsmentioning
confidence: 99%
“…Four (Richardson and Puri, 2002;Stevens et al, 2003;Sinn, 2007;Johnson et al, 2009) out of five (Raz et al, 2009) randomized controlled trials supplementing a mix of n-3 fatty acids (120-730 mg/d) and n-6 fatty acids (60 to 135 mg/d) showed improvements on self-reported ADHD symptoms. Six more studies of varying quality, two of them were open-label studies, supplemented n-3 fatty acids alone (Voigt et al, 2001;Hiramaya et al, 2004;Joshi et al, 2006;Sorgi et al, 2007;Vaisman et al, 2008;Gustafsson et al, 2010). Only the openlabel studies showed a significant effect of ALA (400 mg/d) or very high doses of EPA/DHA (16 g/d) on behavioural outcomes (Joshi et al, 2006;Sorgi et al, 2007).…”
Section: Evidence From Diseased Populationsmentioning
confidence: 99%